2005
DOI: 10.1182/blood-2004-10-3867
|View full text |Cite
|
Sign up to set email alerts
|

Sustained correction of disease in naive and AAV2-pretreated hemophilia B dogs: AAV2/8-mediated, liver-directed gene therapy

Abstract: Adeno-associated virus 8 (AAV8), a new member of the AAV family isolated from nonhuman primates, is an attractive candidate for hepatic gene transfer applications because of 10-to 100-fold improved transduction efficiency in mouse liver models. Additionally, AAV8 has lesser frequency of pre-existing immunity in humans. These properties could solve some of the problems associated with AAV2 vectors. The benefits of AAV8 demonstrated in mouse models, however, have not been confirmed in larger animals. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
147
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(153 citation statements)
references
References 31 publications
5
147
1
Order By: Relevance
“…In vitro NAb assays, including those performed in this study, have demonstrated a lack of cross-reactivity between different types (22,23,26). The utilization of other types of AAV vectors to overcome AAV2 NAb activity has been performed in several animal models (27,55,64). Consistent with these studies, AAV1, AAV4, and AAV5 were found to transduce skeletal muscle regardless of preimmunization with AAV2 (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…In vitro NAb assays, including those performed in this study, have demonstrated a lack of cross-reactivity between different types (22,23,26). The utilization of other types of AAV vectors to overcome AAV2 NAb activity has been performed in several animal models (27,55,64). Consistent with these studies, AAV1, AAV4, and AAV5 were found to transduce skeletal muscle regardless of preimmunization with AAV2 (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…1,8,23 The most frequently used hepatocyte-specific promoters, with or without fusion of one or two heterologous enhancer elements, are the human AT promoter, 4,12,26,27 the albumin promoter 28,29 and the LSP promoter. 3,7,9 In this direct comparative study using hydrodynamic and adenoviral gene transfer, we show that the DC172 promoter, consisting of a 890 bp human AT promoter and two copies of the 160 bp a 1 -microglobulin enhancer, combined with two or four copies of the HCR-1 3 0 of the transgene, constitutes the most potent expression cassette. The a 1 -microglobulin/bikunin precursor promoter is weak and ubiquitously active, but expression in PC is potently increased by a hepatocytespecific enhancer located 2.7 kb downstream of the promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional targeting by use of hepatocyte-specific expression cassettes may lead to immunological ignorance or tolerance for the transgene product. [1][2][3] Expression cassettes for hepatocyte-directed transfer have been improved by using new promoterenhancer combinations, [3][4][5][6][7][8][9] inclusion of introns 5,[10][11][12][13] and inclusion of additional transcriptional sequences like scaffold matrix-attached regions (SMAR) and hepatic control regions (HCR). 12,[14][15][16][17][18] However, because different gene transfer vectors, different doses and different transgenes were used in these studies, direct comparative data for different expression cassettes are often lacking and hamper the interpretation of existing literature.…”
Section: Introductionmentioning
confidence: 99%
“…Among several recently isolated serotypes, AAV8 possesses high transduction rate in liver and low preexisting immunity in human population, therefore, is an attractive vector for liver gene delivery. [29][30][31][32][33] Another major advancement in AAV vector development was the discovery that AAV with self-complementary doublestranded genome possessed 10-to 100-fold higher transduction rate in liver than conventional singlestranded AAV. 34,35 We, therefore, decided to construct double-stranded AAV2/8 pseudotyped vector (dsAAV2/8) to deliver shRNAs and to investigate its inhibition effects in HBV transgenic mice.…”
Section: Introductionmentioning
confidence: 99%